(untitled) (Chemical Engineering Research Bulletin, 2013)
Effect of temperature gradients, for an exothermic reaction, inside a catalyst pellet and the pore size distribution on the value of tortuosity factor is studied. The structure of the catalyst pellet is simulated using a two dimensional pore network. Material and energy balances for the pore network are written and discretised using a finite difference scheme. Tortuosity factors obtained for the isothermal and non-isothermal pellets are compared. Significant variation of the estimated tortuosity factor with internal particle temperature gradient and pore size is obtained. DOI: http://dx.doi.org/10.3329/cerb.v16i1.13191 Chemical Engineering Research Bulletin 16(2013) 61-72